Świat pełen bogów: pogaństwo czy politeizm? - Musiał, Danuta (Instytut Historyczny Uniwersytetu Wrocławskiego, 2022)
Terminology is one of the more difficult issues facing academics investigating ancient religious imaginations. The history of the terms "paganism" and "polytheism," as well as the primary caveats associated with their use, are outlined in this article. Although both names are artificial inventions with added meaning, "polytheism" is thought to be less reliant on Christian beliefs.
Keywords: terminologia; pogaństwo; politeizm; chrześcĳaństwo